2001
DOI: 10.2105/ajph.91.5.808
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancy and low birthweight in Ecuador

Abstract: OBJECTIVES: This study assessed the relationship between unintended pregnancy and infant birthweight in Ecuador, differentiating between unwanted and mistimed pregnancies. METHODS: Analyses focused on a subsample of women (n = 2490) interviewed in the 1994 Ecuador Demographic and Maternal-Child Health Survey. Logistic regression was used to assess the relationship between pregnancy intention status and low birthweight after control for other factors. RESULTS: Infants from unwanted pregnancies were more likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Cross-sectional studies generally produce findings that align with longitudinal evidence that children from unintended pregnancies experience worse subsequent health (Eggleston, Tsui and Kotelchuck 2001, Jensen and Ahlburg 1999, Jensen and Ahlburg 2002, Joyce, Kaestner and Korenman 2000b, Kost, Landry and Darroch 1998, Marston and Cleland 2003, Mohllajee et al 2007, Sable et al 1997). However, this is not the case for cross-sectional studies of child mortality, which have shown associations in the opposite direction.…”
Section: Unintended Pregnancy and Child Outcomesmentioning
confidence: 65%
“…Cross-sectional studies generally produce findings that align with longitudinal evidence that children from unintended pregnancies experience worse subsequent health (Eggleston, Tsui and Kotelchuck 2001, Jensen and Ahlburg 1999, Jensen and Ahlburg 2002, Joyce, Kaestner and Korenman 2000b, Kost, Landry and Darroch 1998, Marston and Cleland 2003, Mohllajee et al 2007, Sable et al 1997). However, this is not the case for cross-sectional studies of child mortality, which have shown associations in the opposite direction.…”
Section: Unintended Pregnancy and Child Outcomesmentioning
confidence: 65%
“…Notwithstanding the fact that every unintended pregnancy represents a failure to meet the reproductive health needs of women and their partners, unintended pregnancies unnecessarily expose women to the risks associated with pregnancy, unsafe abortion and childbirth, thereby contributing to maternal mortality and morbidity. Unintended pregnancies have also been associated with adverse outcomes such as low birth weight, preterm birth, postnatal depression and neonatal mortality [211]. …”
Section: Introductionmentioning
confidence: 99%
“…Roma women are poorer, according to a well-described situation of that ethnic minority, which is particularly exposed to higher rates of poverty [35];  Marital status of women, with benefits showed for married women. In fact, the decline in marriage is a well-known and well-documented phenomenon with major consequences for poverty, inequality and the use of welfare programs [36,37];  Educational level of women, which is inversely associated with poverty, i.e., the lower the educational level, the greater the poverty condition [8][9][10][11]33,34];  Differences based on socioeconomic status for entry in parenting, which is related with how the planning of children and willingness of couples to have, or have not, children occurs at the time that the pregnancy happens [14,38];  Most women did not think to become pregnant when they had the last child, described in Portugal [14] and internationally [38], where at least one child after the first one was not planned;  Patterns of utilization of pre-conception and postpar-tum consultations of the last child, with the very poor and poor women presenting lower rates of utilization [26][27][28];  Economic access and especially the results related to the incapacity to access certain health care and/or payment of medication, especially for women, corroborates the results from studies that have shown that the burden of payment for health services constitutes a cause of poverty [21]. According to the above associations extreme poverty, of the type that allows access to special social inclusion subsidies in Portugal, seems associated with: ethnicity [35]; household characteristics, such as size, with each extra person in a household increasing the chance of being poor [10] and income [10,33,34]; personal characteristics, namely the association between low levels of education and higher odds of being poor [10,33,39]; and marital status, with marriage appearing as a protective factor of poverty [36,37].…”
Section: Discussionmentioning
confidence: 99%